Effect of stacking sequence of glass and jute fiber reinforced polymer composites on their low velocity impact properties - Pandian, Amuthakkannan; Hameed Sultan, Mohamed Thariq; Manikandan, Vairavan; Marimuthu, Uthayakumar; Kanagaraj, Arun Prasath; Khan, Tabrej (SAGE Publications, 2022)
This paper investigated the effect of stacking sequence on the low velocity impact behavior of glass and jute fiber reinforced hybrid composites. The hand layup method is used to fabricate the composites with various stacking sequences. The low velocity impact analysis was carried out at various impact energies, namely 5 J, 10 J and 15 J. Dye penetrant inspection (liquid penetrate inspection) was performed to analyses the damage area in the composites. Compression after impact (CAI) testing was conducted to study the compression strength of the composites after the impact. The study revealed that the jute fiber composites exhibited better results in terms of energy absorption, but the damage area of the composites was higher, compared to the other specimens fabricated. Meanwhile, hybrid composite S7 presented high energy absorption and the minimum damage area. To conclude, the hybrid composite S7 appeared to have the optimum formulation, showing better results in energy absorption, with lower damage and higher compression strength.